138k views
0 votes
-2/3 (x-7) = 1/6 (x+1) -3

User MikeOnline
by
5.5k points

1 Answer

1 vote

Answer: x = 9

Explanation:

We will isolate the variable x to solve this equation.

Given:

-2/3 (x-7) = 1/6 (x+1) -3

Distribute:

-2/3x + 14/3 = 1/6 (x+1) -3

-2/3x + 14/3 = 1/6x + 1/6 -3

Combine like terms on the right side using subtraction:

-2/3x + 14/3 = 1/6x - 17/6

Subtract 1/6x from both sides of the equation:

-5/6x + 14/3 = - 17/6

Subtract 14/3 from both sides of the equation:

-5/6x = -15/2

Divide both sides of the equation by -5/6:

x = 9

User Fajran
by
5.9k points